Do women's empowerment and socioeconomic status predict the adequacy of antenatal care? A cross-sectional study in five South Asian countries. Issue 6 (3rd June 2021) - Anik, Asibul Islam; Islam, Md Rashedul; Rahman, Md Shafiur
Abstract : Objectives: Relative to the attention given to improving the measurement of adequacy of antenatal care (ANC) in South Asian (SA) region, the influence of women's empowerment and socioeconomic status (WESES) on adequate ANC services has hardly received any attention. This study aimed to investigate the present scenario of adequacy of ANC in SA and how its adequacy was associated with WESES. Setting and participants: Using the Demographic and Health Survey data set of five SA countries, that is, Afghanistan, Bangladesh, India, Nepal and Pakistan, 48 107 women were selected in this study who received at least one ANC component and had at least one live birth in the 3 or 5 years preceding the survey. Analysis: Multilevel logistic regression models were used to investigate the relationship between adequacy of ANC and WESES. Results: Only 30% women received adequate ANC in SA, ranging from 8.4% (95% CI 7.1% to 9.9%) in Afghanistan to 39.8% (95% CI 37.4% to 42.2%) in Nepal. The poor utilisation of adequate ANC services was most prevalent among the women residing in rural areas and that of poor families as well as low empowerment status in SA countries. Different levels of WESES, that is, highly empowered but poor (adjusted OR (AOR): 1.33; 95% CI 1.18 to 1.49), lowly empowered but rich (AOR: 2.07; 95% CI 1.84 to 2.32) and highly empowered and rich women (AOR: 3.07; 95% CI 2.75 to 3.43), showed significant positive association with adequate ANC services than the poor and low empowered women, after adjusting the potential covariates. Conclusion: As unsatisfactory level of adequate ANC services has been observed in SA region, this study suggests a nationwide comprehensive improvement of women's empowerment status as well as establishment of necessary healthcare centres in remote areas is essential to ensure long-term and sustainable adequacy of ANC services.